The Moss Physcomitrium (Physcomitrella) patens: A Model Organism for Non-Seed Plants. Issue 5 (9th March 2020) - Rensing, Stefan A.; Goffinet, Bernard; Meyberg, Rabea; Wu, Shu-Zon; Bezanilla, Magdalena
Abstract : Studies of P . patens, a powerful non-seed plant model system, have made fundamental contributions to diverse fields, including evolutionary developmental and cell biology. Abstract: Since the discovery two decades ago that transgenes are efficiently integrated into the genome of Physcomitrella patens by homologous recombination, this moss has been a premier model system to study evolutionary developmental biology questions, stem cell reprogramming, and the biology of nonvascular plants. P . patens was the first non-seed plant to have its genome sequenced. With this level of genomic information, together with increasing molecular genetic tools, a large number of reverse genetic studies have propelled the use of this model system. A number of technological advances have recently opened the door to forward genetics as well as extremely efficient and precise genome editing in P . patens . Additionally, careful phylogenetic studies with increased resolution have suggested that P . patens emerged from within Physcomitrium . Thus, rather than Physcomitrella patens, the species should be named Physcomitrium patens . Here we review these advances and describe the areas where P . patens has had the most impact on plant biology.